(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The main goal of the article is to expose the opportunities of the Kasagh River basin tourism-recreational resources. It is targeted to estimate the natural historic-cultural values of the basin. The service infrastructures have been studied and estimated. Besides, the role of ethnic minorities settled in Kasagh basin is very important in the context of tourism sector development.